Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/ncb2221
|View full text |Cite
|
Sign up to set email alerts
|

ARFGAP1 promotes AP-2-dependent endocytosis

Abstract: Two of the best characterized coat proteins are Coat Protein (COP) I and clathrin associated with Adaptor Protein 2 (AP-2), for which no common component has been identified. A GTPase-activating protein (GAP) for ADP-Ribosylation Factor 1 (ARF1), ARFGAP1, is known to act as a component of the COPI complex. Here, we find that distinct regions of ARFGAP1 interact with AP-2 and coatomer (components of the COPI complex). Selectively disrupting the interaction of ARFGAP1 with either of these two coats leads to sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 58 publications
1
46
1
Order By: Relevance
“…Another class of proteins that has been shown to bind clathrin in animal systems is the ADP ribosylation factor GTPaseactivating protein (ARF GAP) family, whose members induce the hydrolysis of GTP bound to ARF and are essential factors to couple vesicle formation with cargo loading (Tanabe et al, 2005;Natsume et al, 2006;Spang et al, 2010;Bai et al, 2011). However, there are no prior reports of plant ARF GAPs binding to clathrin or having a role in vacuolar trafficking.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another class of proteins that has been shown to bind clathrin in animal systems is the ADP ribosylation factor GTPaseactivating protein (ARF GAP) family, whose members induce the hydrolysis of GTP bound to ARF and are essential factors to couple vesicle formation with cargo loading (Tanabe et al, 2005;Natsume et al, 2006;Spang et al, 2010;Bai et al, 2011). However, there are no prior reports of plant ARF GAPs binding to clathrin or having a role in vacuolar trafficking.…”
Section: Introductionmentioning
confidence: 91%
“…Most studies have centered on the prototypical mammalian ArfGAP1, which is involved in COPI vesicle formation. Knowledge about ARF GAPs involved in CCV formation is much more limited, although the basic mechanisms may well be the same (reviewed in Kon et al, 2011), and a recent study found an unexpected involvement of ArfGAP1 also in CCV formation (Bai et al, 2011). The initial hypothesis that ArfGAP1 triggers vesicle coat disassembly by the ARF-GTP to ARF-GDP conversion has been revisited over the last 10 years, and several, more refined models for ARF GAP function have been proposed (reviewed in Nie and Randazzo, 2006;Spang, et al, 2010).…”
Section: Discussion the Molecular Mode Of Action Of Mtv1 And Nev/agd5mentioning
confidence: 99%
“…A positive role for SMAP1 is compatible with the function of other ARF GAP proteins whose knockdown impairs vesicle transport. For example, targeting of ARF GAP1 impaired transferrin endocytosis (30), suggesting an ARF GAP1-dependent but SMAP1/2-independent route of transferrin endocytosis. In any case, our results support a positive role of SMAP1 in vesicle formation and may contribute to the discussion on the putative terminator versus effector functions of ARF GAPs (31,32).…”
Section: Figurementioning
confidence: 99%
“…Immunoprecipitation experiments and GST pulldown experiments were performed as previously described (19,20).…”
Section: Methodsmentioning
confidence: 99%